AI-Enhanced IMC: Leveraging Data Analytics for Targeted Marketing Campaigns - Boinapalli, Narasimha Rao; Farhan, Kazi Ahmed; Allam, Abhishekar Reddy; Nizamuddin, Md.; Sridharlakshmi, Narayana Reddy Bommu (Asian Business Review, 2023)
Data analytics to improve targeted marketing efforts examines how artificial intelligence (AI) transforms Integrated Marketing Communications (IMC). The main focus is AI technology's effects on customization, real-time marketing, and client segmentation. The secondary data-based study reviews academic literature, industry publications, and case studies from Netflix, Coca-Cola, Sephora, and Starbucks. Major studies show that AI improves customization, real-time optimization, and accurate targeting, improving engagement, customer happiness, and campaign performance. However, data privacy, algorithmic prejudice, and ethics are issues. The report emphasizes the need for robust data security and fair AI rules that balance innovation and consumer protection. Responsible AI marketing requires robust legal frameworks and ethical standards to address these difficulties.